PENINGKATAN EKONOMI MASYARAKAT SEKITAR KAWASAN HUTAN GAMBUT DENGAN PEMANFAATAN PURUN - Siti Maimunah; Fahruni Fahruni; Nanang Hanafi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
Degraded peat swamp forest in Central Kalimantan influence the economic activities of community around the forest. The terrible activities of the community have exploited the forest, and it must stop now with more solution to make a new sustainable livelihood. Now, forest can’t support us in increasing the economic values for the community. The effects of losing the forest are the earth temperate will rise, we can’t find wood for tools and also non-timber forest product. The aims of those activities are for indirect protecting activities for the forest area and rehabilitation action with purun cultivation and to optimizing purun for industrial activities of purun handicraft. There are two activities for saving the forest socialization and training of purun handicraft for the community without destroying the last forest it. The activities have done in Rantau Kujang village of South Barito District Central of Kalimantan on 23rd November 2017 supported by Indonesian Climate Changes Trust and Fund (ICCTF) with Focus Group Discussion method and the intensive training for the community about purun cultivation and processing the industrial purun handicraft. The results are community have a more new idea for sustainable livelihood without destroyed their forest. Before our training, the Community only can break their forest, but now they have found more idea for economic activities and sustainable act for the forest. The community needs a support and suggestion to found more livelihood activities with a link for marketing and the right cultivation.